2016
DOI: 10.1093/mnras/stw283
|View full text |Cite
|
Sign up to set email alerts
|

Cross-correlation analysis of CMB with foregrounds for residuals

Abstract: In this paper, we try to probe whether a clean CMB map obtained from the raw satellite data using a cleaning procedure is sufficiently clean. Specifically we study if there are any foreground residuals still present in the cleaned data using a cross-correlation statistic. Residual contamination is expected to be present, primarily, in the galactic plane due to the high emission from our own galaxy. A foreground mask is applied conventionally to avoid biases in the estimated quantities of interest due to foregr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The extragalactic non-Gaussian contributions, including for example the Sunyaev-Zel'dovich (SZ) and lensing effects, besides point sources (secondary CMB anisotropies), are not relevant for the scales considered. In addition, the Planck Galactic mask used here, termed U73, includes the point-sources mask [14,[23][24][25][26]. In this way, our main goal is to test the efficiency of our estimator to constrain primordial NG in the presence of non-Gaussian foreground contaminations from diverse Galactic emissions.…”
Section: Jcap09(2015)064mentioning
confidence: 99%
“…The extragalactic non-Gaussian contributions, including for example the Sunyaev-Zel'dovich (SZ) and lensing effects, besides point sources (secondary CMB anisotropies), are not relevant for the scales considered. In addition, the Planck Galactic mask used here, termed U73, includes the point-sources mask [14,[23][24][25][26]. In this way, our main goal is to test the efficiency of our estimator to constrain primordial NG in the presence of non-Gaussian foreground contaminations from diverse Galactic emissions.…”
Section: Jcap09(2015)064mentioning
confidence: 99%
“…To study Ser-CARTs, we developed a polymerization method that avoids the control issues and harsh conditions previously reported for oligo(serine ester) synthesis. 30,[33][34][35][36][37] Our procedure benefits from the commercial availability of the N-trityl-L-serine lactone monomer (serine lactone) and an organocatalytic ring-opening polymerization (OROP) [38][39][40][41][42][43] strategy, utilizing a thiourea anion catalyst recently developed for the OROP of lactones and cyclic carbonates (Figure 1). 44 Specifically, we found that the OROP of serine lactone with 1 (3,5bis(trifluoromethyl)phenyl)-3-cyclohexylthiourea (TU) and potassium hydride (KH) in the presence of an alcohol initiator proceeds at room temperature in hours to generate tritylprotected poly(serine esters) 5a−9a with predictable molecular weights (M n = 7−17 kDa) and narrow dispersities (Đ = 1.11−1.24), avoiding the previously reported multimodal distributions (Tables 1 and S1).…”
mentioning
confidence: 99%
“…The most accurate current measurements of the CMB temperature fluctuations are part of the third public data release of the Planck collaboration [48], precise data that allow to re-examine many interesting features already reported with diverse CMB data sets [2,[18][19][20][21][22][23][24][25][26][27][28][29][30]51]. Further, CMB products combined with data sets from other cosmological tracers are being used to study models alternative to the flat-ΛCDM model (see, e.g.…”
Section: Datamentioning
confidence: 99%